THE EFFECT OF ACTIVATING BACKGROUND KNOWLEDGE ON STUDENTS’ READING COMPREHENSION IN DESCRIPTIVE TEXT AT THE SECOND GRADE OF MTSN 6 AGAM IN ACADEMIC YEAR 2021/2022 - Memi Cahya Ningsih; Veni Roza; Reflinda; Meylann Melani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The purpose of this research were to find the students’ reading comprehension in descriptive text that taught by using activating background knowledge and to find whether significant differences of student’ who activate background knowledge with the student’ who are not activate the background knowledge on reading comprehension in descriptive text. This was experimental research. The researcher used two classes on this research (experimental class and control class). It means that by comparing two groups by giving a different treatment then giving a test to check whether there was significant effect or not. The population of this research was 278 students, because the population number was big, the researcher took purposive sampling with some consideration. The instrument that used was multiple choice the questions consist of 20 items. T- test was used to analysis the data. The mean score of the data analysis for significant effect of using activating background knowledge was 50,67 in pre-test and 83,67 in post-test. The result shows that to 55,78 compared to level significant 0,05 was 1,70 and it showed that the Ha was accepted. This can be concluded that there was significant effect of using activating background knowledge on students’ reading comprehension in descriptive text.